Theoretical and methodological analysis of the problem of mental development of schoolchildren (Actual Problems of Psychology in Educational Institutions, 2022)
The article presents the general characteristics of the peculiarities of mental development of school-age pupils. It is revealed the classification of mental operations. The strategy of new technologies use in work with different school-age pupils.
Keywords: school age; mental development; mental surgery